2012
DOI: 10.1021/jo301684b
|View full text |Cite
|
Sign up to set email alerts
|

GFP-like Fluorophores as DNA Labels for Studying DNA–Protein Interactions

Abstract: GFP-like 3,5-difluoro-4-hydroxybenzylideneimidazolinone (FBI) and 3,5-bis(methoxy)-4-hydroxy-benzylideneimidazolinone (MBI) labels were attached to dCTP through a propargyl linker, and the resulting labeled nucleotides (dC(MBI)TP and dC(FBI)TP) were used for a facile enzymatic synthesis of oligonucleotide or DNA probes by polymerase-catalyzed primer extension. The MBI/FBI-labeled DNA probes exerted low fluorescence that was increased 2-3.2 times upon binding of a protein. The concept was demonstrated on sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
53
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 68 publications
0
53
0
Order By: Relevance
“…Remarkably, metal nanoclusters can detect natural nucleic acids, such as cancer related mRNAs, directly in living cells [31]. Finally, the use of so-called environmentally sensitive modified nucleosides and nucleotides also offers exciting opportunities for the specific detection of nucleic acids [32][33][34][35][36]. The distinguishing feature of these is enhanced fluorescence upon a change in the local microenvironment.…”
Section: Enzyme-free Hybridization Assays: Specificity In Focusmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, metal nanoclusters can detect natural nucleic acids, such as cancer related mRNAs, directly in living cells [31]. Finally, the use of so-called environmentally sensitive modified nucleosides and nucleotides also offers exciting opportunities for the specific detection of nucleic acids [32][33][34][35][36]. The distinguishing feature of these is enhanced fluorescence upon a change in the local microenvironment.…”
Section: Enzyme-free Hybridization Assays: Specificity In Focusmentioning
confidence: 99%
“…They were able to achieve this owing to the environmentally sensitive intramolecular charge transfer (ICT) between the nucleobase and naphthalene moieties [33]. Other successful examples of environmentally sensitive modified nucleosides include light-up probes for the detection of triplex formation and polarity sensitive probes [34][35][36]. One particularly useful mechanism involves introducing intramolecular conformational changes at the bond between the attached modifications and nucleobase [34,35].…”
Section: Enzyme-free Hybridization Assays: Specificity In Focusmentioning
confidence: 99%
“…One of the most standard methods for labeling nucleic acids involves the attachment of a fluorescent dye to the C5-position of pyrimidine nucleosides through alkynyl linkage, because this enables predictive positioning of the fluorophores in the major groove of duplexes without the loss of Watson-Crick base-paring properties. [9][10][11][12][13][14][15] The fluorescent properties of these nucleosides are mainly dependent on the fluorophores chosen; thus, the specific type of fluorophore that is loaded onto the nucleoside is an essential consideration to best detect the local environmental change of nucleic acids.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent pyrimidine nucleosides containing GFP-like fluorophore at the 5-position have also been reported as an ESF nucleoside for studying DNA-protein interactions. 7 In our continuous efforts to develop practically useful ESF nucleosides, 8 we recently reported that 7-naphthylethynylated 8-aza-7-deaza-2 0 -deoxyadenosine cna A exhibited dual fluorescence emission arising from an intramolecular charge-transfer (ICT) state and a locally excited (LE) state depending upon the coplanarity between naphthalene ring and 8-aza-7-deazaadenine skeleton through ethynyl linker (Fig. 1 discriminate perfectly matched thymine on the complementary strand by a significant shift of emission wavelength to shorter wavelength via probing the differences in microenvironment caused by a structural change.…”
Section: Introductionmentioning
confidence: 99%